User-centric innovation strategies for cultural creative products in China’s rural tourism - Yuzhe Qi; Qing Ni; Jing Zhang; Jiangyue Han; Hongyan Ren (PLoS ONE, 2025)
Cultural creative products play an important role in the revitalization of tourism-oriented rural areas and the preservation of cultural heritage. However, existing products fail to fully meet the diverse needs of consumers and lack a systematic design framework. This study proposes a user-centered framework aimed at guiding the innovation of cultural creative products in China’s rural tourism. During the exploration of user needs, grounded theory was used to identify three core user needs: emotional identification, personalization and uniqueness, and enhancement of quality of life. Using the KANO model, these needs were further categorized into basic needs, performance needs, and excitement needs, clarifying their priorities. In the stage of translating user needs into actionable design elements, the Analytic Hierarchy Process (AHP) was employed to assign weights to each need, and Quality Function Deployment (QFD) theory was used to construct the House of Quality, refining 14 user needs into 9 key design elements. The findings indicate a positive correlation between multifunctional design and ergonomic design, that usability and convenience are closely related to human-machine ergonomics, and that the integration of cultural symbols with emotional design and innovative forms significantly enhances the cultural value and user experience of the products. This study provides a systematic theoretical framework and practical guidance for the innovation of rural cultural creative products, with significant implications for future research and practice.